Proceedings of the 2017 ACM Conference on Economics and Computation 2017
DOI: 10.1145/3033274.3085137
|View full text |Cite
|
Sign up to set email alerts
|

Posted Price Mechanisms for a Random Stream of Customers

Abstract: published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
75
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(77 citation statements)
references
References 23 publications
2
75
0
Order By: Relevance
“…In general single-parameter environments with matroid feasibility constraints (this includes the single item setting we study as a special case), Chawla et al (2010) showed the the revenue of an ESP that uses the posted prices of an SPM as its personalized reserve prices is at least as high as the SPM's revenue. This, combined with the recent result of Correa et al (2017) showing that SPM can achieve a 0.745 fraction of MyeRev in the i.i.d. setting with possibly irregular distributions, shows that ESP can also achieve at least a 0.745 approximation factor in the i.i.d.…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…In general single-parameter environments with matroid feasibility constraints (this includes the single item setting we study as a special case), Chawla et al (2010) showed the the revenue of an ESP that uses the posted prices of an SPM as its personalized reserve prices is at least as high as the SPM's revenue. This, combined with the recent result of Correa et al (2017) showing that SPM can achieve a 0.745 fraction of MyeRev in the i.i.d. setting with possibly irregular distributions, shows that ESP can also achieve at least a 0.745 approximation factor in the i.i.d.…”
Section: Introductionsupporting
confidence: 72%
“…In this paper we establish the first separation results for ESP: we show that even in the case of distributions drawn i.i.d., but not necessarily satisfying the regularity condition, the ESP cannot achieve more than a 0.778 fraction of MyeRev in general. Combined with the result from Correa et al (2017) that ESP can achieve at least a 0.745 fraction of MyeRev, this nearly bridges the gap between upper and lower bounds on ESP's approximation factor. * Google Research.…”
mentioning
confidence: 62%
“…Going beyond 1 − 1/e has been challenging. Only recently, Abolhasani et al [1] and Correa et al [8] improve this factor for the single item i.i.d. setting.…”
Section: Related Workmentioning
confidence: 99%
“…In terms of upper bounds it was unclear until very recently whether there was a separation between prophet secretary and the i.i.d prophet inequality, where the random variables are identically distributed. For this problem, Hill ad Kertz [18] provided the family of worst possible instances from which [20] proved the largest possible bound one could expect is 0.7451 and Correa et al [6] proved that this value is actually tight. Very recently, Correa et al show that no algorithm can achieve an approximation factor better than √ 3 − 1 ≈ 0.71 for the prophet secretary problem (see the full version of [9]).…”
Section: Introductionmentioning
confidence: 99%